PERAN PEMBELAJARAN BERBASIS MASALAH BERBANTUAN MEDIA VIDEO UNTUK MENINGKATKAN PEMAHAMAN KONSEP SISWA KELAS V SD PADA MATERI SIKLUS AIR. - Amalia, Nindia; Sunaengsih, Cucun; Sujana, Asep (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
One of the problems that occurs in science learning is that in the process of delivering material from teachers to students, they still use conventional learning models, resulting in less than optimal understanding of concepts and students. Efforts that can be made to improve students' understanding of concepts are by implementing a problem-based learning model assisted by video media to help students become smarter in solving problems, making it easier to master the material. The aim of this research is to determine the role of the problem-based learning model assisted by video media in increasing students' conceptual understanding. The method used is a quasi-experiment with a Nonequivalent Control Group Design. The number of participants was 60 class V students in one of the elementary schools in Patrol District. The research instruments used were concept understanding tests and observation sheets consisting of teacher performance sheets and student activities. The research results show: 1) The implementation of learning using a problem-based learning model obtains very good criteria between teacher performance and student activity. 2) The average N-Gain results show that there is a difference in the increase in students’ mastery of concepts between the experimental class and the control class, the experimental class has a highter average N-Gain than the control classs.